Book of the dead - Cornwell, Patricia Daniels (Cornwell, Patricia Daniels. Scarpetta series., 2007)
The "book of the dead" is the morgue log, the ledger in which all cases are entered by hand. For Kay Scarpetta, however, it is about to have a new meaning. Fresh from her bruising battle with a psychopath in Florida, Scarpetta decides it's time for a change of pace-not only personally and professionally, but geographically. Moving to the historic city of Charleston, South Carolina, she opens a unique private forensic pathology practice, one in which she and her colleagues-including Pete Marino and her niece, Lucy-offer expert crime-scene investigation and autopsies to communities that lack local access to competent death investigation and modern technology. It seems like an ideal situation, until the new battles start-with local politicians, with entrenched interests, with someone whose covert attempts at sabotage are clearly meant to run her out of town. And that's even before the murders and other violent deaths begin. A young man from a well-known family jumps off a water tower. A woman is found ritualistically murdered in her multi-million-dollar beach home. The body of an abused young boy is discovered dumped in a desolate marsh. Meanwhile, in distant New England, problems with a prominent patient at a Harvard-affiliated psychiatric hospital begin to hint at interconnections that are as hard to imagine as they are horrible.